Kemunculan Ilmu Tafsir - Habibia Adama (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2021)
The main and first interpretation of the Qur'an is none other than the Sunnah. Namely the words (aqwal) and deeds (af'aal) of the Prophet and the actions of others. Namely his friends, which they did in front of him, and then left it alone, he did not prevent (taqrir). The companions who lived at the time of the Prophet, it was not too difficult to find sources in interpreting the verses of the Qur'an. They simply asked the Messenger of Allah. Therefore, the sources of interpretation are limited to four kinds, namely: the Qur'an, the Prophet Muhammad, Ijtihad and the power of Istinbath and the People of the Book.